Can social scientists be the change agents for diabetes prevention? Diabetes-related knowledge, attitude, and practice among social scientists - Shetty, Raman; Jena, Biranchi; Kadithi, Adibabu (Journal of Social Health and Diabetes, 2013)
Introduction:Diabetes is an emergency in slow motion in India. There is an urgent need of improving awareness and education on diabetes in the community and the social scientist working in the community health are the important group to make this happen.Objectives:To assess the prevalence of diabetes among the social scientists and measure their knowledge, attitude, and practice (KAP) on diabetes.Materials and Methods:A delegate of social scientists attending a national conference on social science and health were screened for random blood sugar and a survey was conducted through a structured self-answered questionnaire on KAP in diabetes. Excel Microsoft Office 2010 package was used for descriptive analysis.Results:A total of 245 social scientists attended the conference; of them, 211 (86%) social scientists voluntarily participated in diabetes screening, and among them, 99 (47%) voluntarily responded on KAP questionnaire. Prevalence rate of diabetes among social scientists was found to be 9.5% and the study revealed that the knowledge was fair, attitude was positive, and practice was good among the social scientists working in the field of social health.Conclusion:The social scientists could be the Change Agents for the changing diabetes in the community through appropriate strategies involving them.
Keywords: Change agents; diabetes; knowledge attitude and practice; social scientist